Effect Of Floral Preservatives On Vase Life Of Gerbera Cut (Gerbera Jamesonii L.) Cv. “Dana Allen” (Applied Biological Research, 2016)
The present study, conducted in the Department of Horticulture, J.A.U.,  Junagadh (India) was aimed to assess the effect of floral preservatives  on the vase life of cut gerbera (Gerbera jamesonii L.)cv. ‘Dana Allen’.  The experiment was laid out in a completely randomized design with  three replications and nineteen treatment-combination comprising of  five floral preservatives viz., sucrose (2 and 3%), 8-HQC [8-hydroxy  quinoline citrate] (150 and 200 mg L-1), Al2SO4 (25 and 50 mg L-1),  AgNO3 (15 and 25 mg L-1) and Co(NO3)2 (180 and 270 mg L-1) along  with an untreated control. The vase solution of 8-HQC @ 200 mg L-1 +  2% sucrose enhanced all the qualitative parameters and improved vase  life of gerbera. The vase life could be extended upto 13.6 days of cut  gerbera. This treatment improved fresh flower weight by 112.3, 104.2,  88.2, 67.1% on 3, 6, 9 and 12th day of vase, respectively. The treatment  of 8-HQC @ 200 mg L-1 + 2% sucrose resulted in maximum total  solution uptake (61.26 mL), flower diameter on 3rd day of vase (11.39 cm) and 50% opening of disc florets (7.28 days), 75% opening of discflorets (8.95 days) and 100% opening of disc florets (11.52 days) in gerbera. It may be concluded that holding solution of 8-HQC along with sucrose may help in extending the vase life of gerbera cut flowers.
Keywords: Al2SO4; AgNO3; Co(NO3)2; gerbera; 8-HQC; sucrose; vase life